PSYCHOLOGICAL EXPERIENCE OF CLIENTS DIAGNOSED WITH GLAUCOMA IN TWO SELECTED EYE CLINICS IN ACCRA, GHANA - Bruce, Daniel; Eshun, V. Mawuli (International Journal of Research -GRANTHAALAYAH, 2017)
The aim of this study was to find out the prevalence of psychosocial problems among persons living with glaucoma and also find out whether socio-demographic characteristics of glaucoma patients significantly affect their levels of psychosocial distress. The cross-sectional survey design was chosen. One hundred (100) patients with glaucoma were selected from two Eye clinics in Accra as the sampled population. One-Way ANOVA, independent t-test and Pearson correlation were used for data analysis. Results from the analysis showed that 99% of the patients reported mild to extremely severe depression. One percent (1%) of the sample reported normal depression levels. It was also observed from the analysis that 75% of the patients reported mild to extremely severe anxiety levels and, 25% reported normal anxiety levels. On stress levels, 45% of glaucoma patients reported mild to severe stress levels whilst 55% of reported normal stress levels. Further analysis showed that female glaucoma patients reported higher depression, anxiety and stress levels than male glaucoma patients, younger glaucoma patients reported higher depression, anxiety and stress levels than older glaucoma patients. However, no statistically significant differences exist among Glaucoma patients who are employed, unemployed and self-employed in their depression and anxiety levels but differed significantly on their stress levels. No statistically significant differences exist among Glaucoma patients who are single, married, widowed and divorced in their depression and anxiety levels but differed significantly on their stress levels. Additionally, there is a significant positive relationship between patients’ social distress and emotional distress (DASS). It is concluded that there is substantial level of psychosocial distress among patients with glaucoma. Patients’ age, sex and marital status significantly affecting their psychosocial distress and therefore, psychosocial care should be included in the healthcare of these patients.